ETIKA GLOBAL GUNA MENGENDALIKAN KAPITALISME GLOBAL - Laleno, Febry Ferdinan (LOGOS, 2017)
The picture of world economy is increasingly leading to global capitalism thathas been considered as an ideal. Capitalism makes entrepreneurs have the samechance and freedom to optimizing their business in free competition andmarket mechanism. Through this way, they expect that prosperity can be realized. This idealized image becomes gloomy as the world is still colored bythe ongoing economic crisis in this modern era and the facts show that there arestill many people in the world who are living in poverty, unemployment, hunger, and the threat of ecosystem destruction. In this context, ethics is the answer to human needs. Global Ethics according to Hans Küng brings full human values, commitment to life, fair economic order, culture of tolerance, and cooperation among humans. Global Ethics can be a first step for entrepreneurs and policy makers to create a culture of positive economic. The effort to realize a more humane global order should be enforced based on a commitment to a fundamental consensus. This consensus contains the outlines of the new paradima of economic ethics which can manage global capitalism to obtain an economic policy that can serve all mankind for the sustainable future of the world